DETERMINANTS OF POTENTIAL PARKING FEE FRAUD IN THE CITY OF MATARAM - Majdi, Alfin Haerul; Inapty, Biana Adha (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2024)
ABSTRACTParking levy is one of the official sources of revenue for local governments that are collected and managed to improve the social welfare of the people in their area. The potential for parking levy revenue in Mataram City is quite large, but for the last five years the realization of parking levy revenue has never been achieved. The goals of this study were to find out the factors that result in the non-realization of parking levy revenue in Mataram City. The research population is all parking attendants who are officially registered on the parking attendant information system application (Sijukir) with a sample size of 40 parking attendants, sampling using purposive sampling. This research is in the form of quantitative research through questionnaires with multiple linear regression analysis. The theoretical basis used is to use the hexagon fraud theory developed by Vousanis in 2019. The research results state that the variables of economic pressure, supervision and rationalization have a positive effect on the potential parking fee fraud. The ability variable has negative effect on the potential for parking fee fraud, while the arrogant attitude and collusion variables have no effect on the potential for parking fee fraud in Mataram City.Keywords: Fraud Hexagon Theory, Potential Fraud, PAD, Parking Levy ABSTRAKRetribusi parkir adalah satu dari sekian sumber pendapatan resmi pemerintah daerah yang dipungut dan dikelola untuk meningkatkan kesejahteraan sosial masyarakat di daerahnya. Potensi penerimaan retribusi parkir di Kota Mataram cukup besar, tetapi selama lima tahun terakhir realisasi penerimaan retribusi parkir belum pernah tercapai. Tujuan penelitian ini yaitu guna meninjau faktor-faktor yang menyebabkan kegagalan realisasi pendapatan retribusi parkir di Kota Mataram. Populasi penelitian adalah semua juru parkir yang terdaftar secara resmi pada aplikasi Sistem Informasi Juru Parkir (Sijukir) dengan jumlah sampel yaitu 40 juru parkir, pengambilan sampel menerapkan purposive sampling. Penelitian ini berupa penelitian kuantitatif melalui kuesioner dengan analisis regresi linier berganda. Landasan teori yang digunakan yaitu menggunakan theory fraud hexagon yang digagaskan oleh Vousanis pada tahun 2019. Hasil penelitian menyatakan bahwa variabel tekanan ekonomi, pengawasan dan rasionalisasi berpengaruh positif terhadap potensi fraud retribusi parkir. Variabel kemampuan berpengaruh negatif terhadap potensi fraud retribusi parkir, sedangkan variabel sikap arogan dan kolusi tidak berpengaruh terhadap potensi fraud retribusi parkir di Kota Mataram.Kata Kunci: Fraud Hexagon Theory, Potensi Fraud, PAD, Retribusi Parkir